Optimizing Sustainable Rural Tourism: Key Factors for Development in Semi-Arid Regions (A Case Study of Abadeh County) - Omid Khademhosseini; Bijan Rahmani; Shahriar Khaledi; Ali Osanlu (برنامه ریزی فضایی)
AbstractBackground: Tourism plays a crucial role in rural development, serving as a valuable approach for economic growth. Effective development in this sector requires a thorough understanding of both internal and external factors to ensure stability. The semi-arid regions of Iran present unique conditions for the advancement of tourism. Purpose: This research aimed to identify optimal strategies for developing sustainable rural tourism in Iran's semi-arid areas, specifically focusing on Abadeh County. The study analyzed internal and external factors to provide actionable insights. Research Method: The research employed a quantitative, descriptive-analytical approach through surveys. The statistical population consisted of experts from various departments in Abadeh County with a sample size of 50 participants determined using the snowball sampling method. Data were collected using a researcher-designed questionnaire that included internal and external factors. Analyses were conducted using SWOT, AHP, and VIKOR models. Findings: The results indicated that the key strengths, weaknesses, opportunities, and threats affecting sustainable rural tourism development included: the spirit of ethnocentrism and collectivism in villages (final weight: 0.388); a lack of tourist accommodations in villages (final weight: 0.427); the potential for attracting private sector investment (final weight: 0.375); and the challenges posed by drought and water scarcity in recent years (final weight: 0.523). The most effective strategy identified for the development of sustainable rural tourism in semi-arid areas was diversification, particularly focusing on attracting investment and enhancing tourism branding. Additionally, the VIKOR model identified the villages of Bidak and Firuzi as top priorities for implementing effective diversification strategies in tourism development. Keywords: Strategy, Sustainable Tourism, Rural Development, Semi-Arid Areas, Abadeh County. IntroductionIn the semi-arid regions of Iran, the sustainability challenges posed by climatic and environmental conditions are particularly significant. Tourism in these rural areas offers a promising solution to mitigate environmental impacts and tensions as it fosters economic diversification and reduces residents' reliance on natural resources. Abadeh County, a notable semi-arid area, holds considerable potential for tourism development. The villages within this region boast various assets, including ethnic and cultural diversity, ecotourism attractions, a culture of hospitality, handicrafts, community cooperation, and strategic geographic locations. To harness these strengths, it is essential to create a framework that aligns with tourism objectives, enabling rural areas in semi-arid regions to achieve sustainability. Developing optimal strategies that consider both the capacities and limitations of Abadeh County's villages is crucial. A thorough understanding of the tourism landscape will not only clarify the current situation, but also inform the strategies and priorities necessary for advancing rural tourism. This research aimed to explain optimal strategies for developing sustainable rural tourism in the semi-arid areas of Iran, focusing specifically on Abadeh County through an analysis of internal and external factors. Materials & MethodsThis study employed a descriptive-analytical research method classified as applied research based on its objectives. Data were collected through a survey using a structured questionnaire. The validity of the questionnaire was assessed by experts, while reliability was evaluated by administering the questionnaire to a sample outside the primary statistical group. For reliability testing, 30 individuals were randomly selected from outside the main sample and the data analysis confirmed a Cronbach's alpha coefficient of greater than 0.70. The statistical population consisted of experts from various departments in Abadeh County. Due to research constraints, 50 experts were identified and surveyed using the snowball sampling method. Data analysis was conducted by utilizing the SWOT model, AHP model, and VIKOR method. Research FindingsDevelopment of sustainable rural tourism is influenced by a variety of promoting and hindering factors. Among the positive factors (strengths and opportunities) were the spirit of ethnocentrism and collectivism in the villages, diversity of rural tourism attractions, hospitality culture of the local residents, a potential for private sector investment, and enhancement of income and employment opportunities for villagers. Additionally, the region possessed a significant potential for nomadic tourism and branding rural tourism. Conversely, the main inhibiting factors (weaknesses and threats) included a lack of tourist accommodations, insufficient rural tourism services and facilities, limited awareness of the region’s tourism potential, drought, water scarcity, and emergence of a new communication route between Isfahan and Shiraz, alongside the region's hot and dry climate. Each of these factors significantly impacted the process of sustainable rural development through tourism. Effective management and mitigation of tensions in this area were crucial. Given the interplay between promoting and inhibiting factors, it was possible to leverage the strengths and opportunities to address and reduce the weaknesses and threats.Analysis of the results indicated that the most critical strategies for developing sustainable rural tourism in the semi-arid regions of Iran centered around diversification. These strategies focused on capitalizing on opportunities while minimizing weaknesses. The analysis of proposed strategies for the villages of Abadeh revealed that attracting investment to enhance rural infrastructure was the most vital diversification strategy. Additionally, prioritization of the villages for implementing these diversification strategies identified Bidak, Firouzi, and Heshmatiyeh as the top three priorities for the execution of effective strategies. Discussion of Results & ConclusionThe findings indicated that the semi-arid areas studied possessed a range of limitations and capacities concerning tourism development. It was crucial to acknowledge these limitations and address them by leveraging available opportunities and driving factors in rural tourism. The region held significant potential for tourism, which could contribute to the sustainability of its villages. The optimal strategy identified was a diversification strategy where weaknesses were mitigated by capitalizing on opportunities. To effectively implement this strategy, it is recommended that planning for the villages be prioritized based on their tourism potential. Additionally, a comprehensive approach to tourism advertising and branding for semi-arid rural areas should be developed and executed to enhance visibility and attract visitors.